Магніторезонансні та трибологічні властивості органопластів на основі співполімеру БСП-7 - Graschenkova, M.O.; Tomina, A.-M.V.; Burya, O.I.; Krasnovyd, S.V.; Konchyts’, A.A.; Shanina, B.D. (Publishing house "Academperiodika", 2023)
The properties of the copolymer BSP-7, high-strength and high-modulus Kevlar-like organic fibers (OFs) Terlon and Vniivlon as fillers, and composites BSP-7/OF have been studied using the electron paramagnetic resonance method. The presence of various defects and magnetic impurities is detected in the raw materials and the manufactured composites. Their properties are determined, and the influence of the matrix interaction with the fillers and the environment on them is revealed. A considerable concentration of nitrogen-containing radicals is detected in Terlon, which are associated with the presence of diamine monomers in its structure and which can negatively affect the physical and mechanical characteristics of composites. On the basis of the obtained data, effective BSP-7/OF organoplastics are developed. The measurements of their tribological properties show that the addition of OFs in an optimal concentration to the BSP-7 polymer matrix brings about a substantial reduction of the friction coefficient, the linear wear intensity, and the heat generation. The best results are obtained for composites with Terlon, which is explained not only by its higher elastic modulus, but also a high degree of structural crystallinity, which is in contrast to Vniivlon with its almost amorphous heterocyclic structure. In addition, the process of composite synthesis suggests the application of rather high temperatures and pressures; as a result, nitrogen radicals of Terlon are destroyed, and their negative impact on the long-term stability of composite parameters becomes eliminated.